STRATEGI PENGEMBANGAN MINAT PEMBELIAN MELALUI PENINGKATAN KEPERCAYAAN NASABAH BCA - Ningwulan, Eka Puspita; Widyastuti, Sri; D, Derriawan (SEKOLAH PASCASARJANA PRESS, 2017)
The rapid progress of the banking world makes the community as a consumer banking services have a large selection of banking companies that can be selected according to their needs. Equality of products, features, or service convenience makes banking into a homogeneous industry, to excel in a homogeneous industry, one way is to provide different types and quality of service between a bank and another bank. The banking world recognizes the importance of obtaining and maintaining customer confidence for the success of the bank business and the benefits of each product offered by the bank requires a marketing strategy, this is done so that the public knows and has the interest to buy the benefits of the products offered in accordance with their needs and desires. This study uses four variables, namely service quality, trust, marketing mix and buying interest. The purpose of this research is to analyze the strategies to increase buying interest through service quality and marketing strategy through customer trust. The method used is descriptive and causality method, data collection techniques are done by giving questionnaires to 250 customers who have done transactions in the BCA Cash office in Depok area and in the analysis using Structural Equation Modeling (SEM) Amos 21. The results showed that service quality had a positive influence on trust, but did not have a positive influence on purchasing intention, and marketing mix has a positive effect on trust and purchasing intention